Health protection of health care workers from the prospective of ethics, science and good medical practice. Opinions from stakeholders in health care settings / La tutela della salute nei lavoratori della Sanità: tra etica, scienza, buone prassi. Le opinioni di manager nel settore della sanità e di professionisti della salute occupazionale - Porru, S.; Cannatelli, P.; Cerioli, et al., B (La Medicina del Lavoro, 2012)
Fitness for work (FFW) in health care workers poses multidisciplinary challenges because of management problems, scientific and ethical implications and the implementation of preventive interventions in health care settings. All the relevant stakeholders, including the General Manager, Medical Director, worker’s representative, the person responsible for prevention and protection, forensic medicine expert, the person responsible for prevention and health safety at public administration level, commented on: danger to third parties; FFW formulation; human resource management; stress; professional independence; role of the person responsible for prevention and protection and of the person responsible for prevention at public administration level; professional responsibilities. Opinions are reported regarding the main problems related to the role of the Occupational Physician in FFW formulation, such as the difficult balance between autonomy and independence, limited turnover and aging of workforce, need of confidentiality and respect for professional status of the HCW, prevalence of susceptibility conditions, rights and duties of stakeholders. The most significant result was the request by the Lombardy Region for more quality in risk assessment and health surveillance; to maintain uniform conduct over all the local health authorities, to allow the board in charge of examining appeals against FFW to fully cooperate with the occupational physician; due attention to the person/worker; the opportunity to convene referral boards for complex FFW management; the challenge of stress management and the need for an observatory for psychological discomforts; the importance of the ICOH Code of Ethics and avoidance of conflicts of interests; the need for individual risk assessment and risk management; the concept of sharing responsibilities and of a real multidisciplinary approach. La tutela della salute nei lavoratori della Sanità: tra etica, scienza, buone prassi. Le opinioni di manager nel settore della sanità e di professionisti della salute occupazionale La formulazione del giudizio di idoneità (GI) nei lavoratori della sanità rappresenta una sfida multidisciplinare, in considerazione di problematiche gestionali, implicazioni etiche e scientifiche, l’attuazione degli interventi preventivi nelle strutture sanitarie. Sono state coinvolte le più rilevanti figure professionali ed i portatori di interesse negli ambienti di lavoro sanitari, ovvero direttore generale, direttore sanitario, rappresentante dei lavoratori per la sicurezza, responsabile del servizio di prevenzione e protezione, medico legale, dirigente regionale unità prevenzione e tutela sanitaria. Le opinioni hanno riguardato in particolare: rischio verso terzi, formulazione GI, gestione risorse umane, stress, indipendenza professionale, ruolo responsabili servizio di prevenzione e protezione, responsabilità professionale. Sono state analizzate le problematiche principali in relazione al ruolo del medico competente nella formulazione del GI, ovvero la ricerca di un equilibrio tra autonomia professionale ed indipendenza, turnover limitato, invecchiamento forza lavoro, necessità di privacy, rispetto professionalità dei lavoratori, prevalenza condizioni di ipersuscettibilità, diritti e doveri delle parti coinvolte. Di particolare rilievo: il richiamo della Regione Lombardia a maggiore qualità nelle attività di valutazione del rischio e sorveglianza sanitaria; la ricerca di maggiore uniformità di condotta delle ASL e di cooperazione tra medico competente e commissioni incaricate nella gestione dei ricorsi contro i GI; attenzione alla persona/lavoratore; opportunità di convocare commissioni per la gestione di GI complessi; criticità nella gestione dello stress e la necessità di un osservatorio per disagi psicologici; importanza del Codice Etico ICOH e necessità di evitare conflitti di interesse; valutazione del rischio e gestione del rischio individuali; condivisione di responsabilità e di un vero approccio multidisciplinare.